2017
DOI: 10.3390/plants7010001
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Flavonoids and Related Compounds in Cedrus brevifolia A. Henry ex Elwes & A. Henry Needles. Inhibitory Potencies on Lipoxygenase, Linoleic Acid Lipid Peroxidation and Antioxidant Activity

Abstract: The phytochemical analysis of the polar extracts of Cedrus brevifolia needles yielded 20 compounds, namely from the methanol extract we isolated three flavonoids (1–3), one hydrolysable tannin (4), eleven phenolic derivatives (5–15) and one apocarotenoid (16), while from the methanol: water (5:1) extract we isolated four flavonoids (17–20). Chemical structures of all isolated compounds were determined by 1D, 2D-NMR (1 Dimension, 2 Dimensions Nuclear Magnetic Resonance) and UV-Vis (Ultraviolet-Visible) spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The methanoic extract of this plant is rich in benzoate glucoside, 2-methoxy-phenyl-β-D-glucoside, abscisic alcohol glucoside,2-methoxy-phenyl-β-D-glucoside, benzoate glucoside, raspberry ketone, taxifolin, 3,4-dimethoxyphenyl-β-D-glucoside, 4-hydroxybenzoic acid 4-O-β-D-glucoside, benzyl-β-D-rutinoside, isorhamnetin 3-O-β-D-glucoside, astragalin, glucoside, (−)-catechin, trans-vaginoside, p-coumaric acid, p-anisic acid and benzyl-β-D-glucoside. The aqueous extract of the same plant is rich in syringetin 3-O-β-D-glucoside, kaempferide-3-O-β-rutinoside, tiliroside and kaempferol-3-O-β-rutinoside (Douros et al 2018). The analysis of volatile compounds in heartwood, sapwood and resin of C. Brevifolia has shown that heartwood and bark have an important amount of hydrocarbon sesquiterpenes (70.4% and 74.7%, respectively) and oxygenated sesquiterpenes (71.7%, 7.5%).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The methanoic extract of this plant is rich in benzoate glucoside, 2-methoxy-phenyl-β-D-glucoside, abscisic alcohol glucoside,2-methoxy-phenyl-β-D-glucoside, benzoate glucoside, raspberry ketone, taxifolin, 3,4-dimethoxyphenyl-β-D-glucoside, 4-hydroxybenzoic acid 4-O-β-D-glucoside, benzyl-β-D-rutinoside, isorhamnetin 3-O-β-D-glucoside, astragalin, glucoside, (−)-catechin, trans-vaginoside, p-coumaric acid, p-anisic acid and benzyl-β-D-glucoside. The aqueous extract of the same plant is rich in syringetin 3-O-β-D-glucoside, kaempferide-3-O-β-rutinoside, tiliroside and kaempferol-3-O-β-rutinoside (Douros et al 2018). The analysis of volatile compounds in heartwood, sapwood and resin of C. Brevifolia has shown that heartwood and bark have an important amount of hydrocarbon sesquiterpenes (70.4% and 74.7%, respectively) and oxygenated sesquiterpenes (71.7%, 7.5%).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The structures of all the compounds annotated on the heat map were confirmed by checking for all carbon atoms of the neighboring correlations in HSQC, HMBC, and COSY spectra. Other metabolites reported in the genus Cedrus [37] were finally searched by complementary LC-MS analyses, leading to the annotation of catechin, taxifolin, and astragalin in the less polar fractions and syningetin-3-O-glucoside and kaempferol-3-O-rutinoside in the medium polar fractions. The work presents a 13 C-NMR dereplication process permitting the characterization of major compounds of a natural extract diluted in glycerin.…”
Section: Dereplication Of a Genuine Natural Extract Diluted In Glycerinmentioning
confidence: 99%
“…This database contains more than 3000 compounds to date and associates structures to the predicted NMR chemical shifts of the proton and carbon atoms, as calculated by the ACD/Labs predictor. A literature survey was carried out on the genus Cedrus, resulting in 40 metabolites stored in the database [37][38][39][40]. A tolerated 13 C-NMR chemical shift difference between the predicted database spectrum and the real spectrum was established at 2 ppm.…”
Section: Data Processingmentioning
confidence: 99%
“…This is further explored in the articles by Navarro and colleagues [ 13 ] as well as Douros and colleagues [ 14 ], who demonstrate the broad roles of flavonoids in plants that have been used traditionally as medicinal plants like Phyllanthus acuminatus and Cedrus brevifolia , respectively. The structure–function relationships of known flavonoids are addressed in the article by Gutiérrez-Grijalva and colleagues [ 15 ], who demonstrated an array of function of flavonoids extracted from the oregano group of medicinal plants, and their dependency on specific modifications of the flavonoid backbone.…”
mentioning
confidence: 99%